High-performance photodetector based on hybrid of MoS2 and reduced graphene oxide. (26th July 2018) - Kumar, Rahul; Goel, Neeraj; Raliya, Ramesh; Biswas, Pratim; Kumar, Mahesh
Abstract: 2D materials are a promising new class of materials for next generation optoelectronic devices owing to their appealing optical and electrical properties. Pristine molybdenum disulfide (MoS2 ) is widely used in next generation photovoltaic and optoelectronic devices, but its low photo-dark current ratio prevents its use in highly efficient photo detection applications. Here, we decorated crumpled reduced graphene oxide (rGO) particles on a large-area vertically aligned MoS2 flake network to enhance the performance of the MoS2 -based photodetector by forming multiple nanoscale p–n heterojunctions. The rGO/MoS2 device exhibited a significantly improved photoresponsivity of ∼2.10 A W −1 along with a good detectivity of ∼5 × 10 11 Jones (Jones = cm Hz 1/2 /W) compared to that of the pristine MoS2 photodetector in ambient atmosphere. Moreover, the rGO/MoS2 photodetector showed a fast response of ∼18 ms with excellent stability and reproducibility in ambient air even after three months. The high performance of the photodetector is attributed to enhanced photoexcited carrier density and suppressed photo generated electron–hole recombination due to the strong local built-in electric field developed at the rGO/MoS2 interface. Our results showed that integration of rGO with MoS2 provides an efficient platform for photo detection applications.